(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
The year I earned my elementary Montessori teaching license is the same year I became a single mother with three children, ages 2-7, living in a home I could no longer afford on my meager income.1 I could only afford to stay in my large Victorian home if I rented out a bedroom or two, so I advertised in the local paper and had a college athlete inquire about renting a room, for at 100/month including utilities, two blocks from campus; it was a steal! This American soccer (football) player was excited about the possibility of living in our home as we interviewed each other, however, he returned the next day to inform me his coach had forbidden him from renting a room from me. “Really?” I responded, incredulously. “Why?” “Because you are a Montessori teacher,” he informed me, sheepishly. I was dumbfounded! Most American’s associate Montessori schools with pre-school age children, or maybe children with special needs, and neither association causes concerns. I asked, “Who is your coach?” The soccer player informed me he was an elderly man from Germany. I searched my memory for what I had recently learned about Dr. Montessori’s history in my training program and asked: “Was he worried about me being a liberal or a Fascist?” The answer was, “Fascist.” I thanked him for coming by and at least letting me know the reason I’d lost a renter.